A CRITICAL DISCOURSE ANALYSIS OF USTADZ KHALID BASALAMAH’S LECTURE FRAGMENT ON YOUTUBE ABOUT “DURHAKA KEPADA ORANG TUA KARENA ISTRI” - Muftihaturrahmah Burhamzah; Nelly Nelly; Alamsyah Alamsyah (Al-Qalam, 2021)
Religious lecture nowadays can be found not only by joining Tablighi Jema’ah in the mosque but also by searching the desired religious lecture theme on YouTube, delivered by the desired ustadz. Even though sometimes the content of the lectures found on YouTube are not in their full version. However, the messages can be received. The theme about wife as the cause of disobedience to parents still becomes a central and popular theme to be delivered by ustadz nowadays. This phenomenon can be related to the nature of a woman as a wife who mostly found difficulty adapting to their spouse's family because of her nature to be dominantly self-controlled by feelings. This study aims to critically analyze the discourse of Ustadz Khalid Basalamah Lecture fragment found on YouTube about wife as the cause of disobedience to parents. This study was conducted by analyzing three aspects of Fairclough's Critical Discourse Analysis Method, namely textual analysis (microstructural analysis), discursive practice analysis (mesostructure analysis), and socio-cultural analysis (macrostructural analysis). The study found that the discourse is: (1) using forbidding words repeatedly to show reinforcement of the messages, (2) distributing messages delivered by Ustadz Khalid Basalamah, who is believed in having 'power' to deliver a religious lecture to Muslims as the consumer by his way that is by persuading the audience to think logically, (3) Have important messages to be delivered in building a harmonious family and future society